Kajian Islam tentang Partisipasi Orang Tua dalam Pendidikan Anak - Mohammad Roesli; Ahmad Syafi'i; Aina Amalia (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The purpose of this study is to remember each party about parent participation in improving learning activities in education by containing theoretical discussion about the problems identified, such as the study of parent participation, the form of participation of parents and study of learning activities with factors that is in education, learning is a basic need in human life. Humans without learning, will not be able to live as human beings especially for children in terms of spiritual tarbiyah, tarbiyah adabiyah, tarbiyah aqliyah, tarbiyah jismiyah.